Hydrocarbon Synthesis via Photoenzymatic Decarboxylation of Carboxylic Acids - Zhang, Wuyuan; Ma, Ming; Huijbers, Mieke M E; Filonenko, Georgy A; Pidko, Evgeny A; van Schie, Morten; de Boer, Sabrina; Burek, Bastien O; Bloh, Jonathan Z; van Berkel, Willem J H; Smith, Wilson A; Hollmann, Frank (Journal of the American Chemical Society, 2019)
A recently discovered photodecarboxylase from Chlorella variabilis NC64A ( CvFAP) bears the promise for the efficient and selective synthesis of hydrocarbons from carboxylic acids. CvFAP, however, exhibits a clear preference for long-chain fatty acids thereby limiting its broad applicability. In this contribution, we demonstrate that the decoy molecule approach enables conversion of a broad range of carboxylic acids by filling up the vacant substrate access channel of the photodecarboxylase. These results not only demonstrate a practical application of a unique, photoactivated enzyme but also pave the way to selective production of short-chain alkanes from waste carboxylic acids under mild reaction conditions.